Concentração, especialização e dinamismo da Indústria Petroquímica Brasileira no período de 1995 a 2005 - (:unkn) unknown (Universidade Federal do Amazonas, 2009)
The petrochemical industry occupies a special position in the national industry in face of his importance for the economical and productive development of the country and of the areas where it settles. The reflections of this dissertation are centered in the analysis of the concentration process, specialization and dynamism on Brazilian petrochemical industry in the period of 1995 and 2005. The adopted methods were the normalized concentration index, location quotient and the shift-share. To test those empiric models the base of personal computer-data of RAIS it was used. The results indicate the areas that hold the Brazilian main petrochemicals poles (Camaçari-BA, ABC-SP and Triunfo-RS) presented high agglomeration levels and specialization with tendency for geographical decentralization in the indicators. Tendency to the gathering and specialization of activities petrochemicals in other areas (especially Alagoas, Manaus and Rio de Janeiro), forming local systems of production, due to the production of the basic raw material and of effects in chain originated by the specific economical activities of each area. It was also verified that there was a slow dynamism of the petrochemical industry national, due to the combination of the structural and differential effects unfavorable, carting in competitive disadvantage.
Keywords: Indústria Petroquímica; Índice de concentração; Quociente locacional; Método estrutural-diferencial; Petrochemical Industry; Index of concentration; Location quotient; Shift-Share Analysis; CIÊNCIAS SOCIAIS APLICADAS